Tinjauan Atas Upaya Pengembangan Kesadaran Merek Pada Produk Nabati - Muhammad Ilyas; Denta Purnama; Ade Yusdira (Jurnal Aplikasi Bisnis Kesatuan, 2023)
ABSTRACT With increasingly widespread market developments, it can lead to increasingly fierce competition between companies and promises new business opportunities and challenges for companies. For this reason, companies are required to compete competitively in terms of creating and maintaining consumer loyalty amid conditions of increasingly high levels of competition in local and global businesses and conditions of uncertainty forcing companies to reach a competitive level in order to be able to win the competition in global business. This Brand Awareness is a form of strategy carried out by the company towards its products which aims to be known and recognized by consumers and can increase the profitability of the company. Consumers will be aware of the existence of a brand on a product if the brand awareness of the product is strong enough. The purpose of this Final Project is to find out: 1) How are efforts to develop brand awareness in Vegetable products; 2) What are the obstacles and how to overcome efforts to develop brand awareness in vegetable products. The results of this Final Project are: 1) Efforts to develop brand awareness for vegetable products are good, management has made every effort to increase brand awareness. 2) Obstacles that occur in efforts to develop brand awareness of vegetable products are able to be overcome by the company quite well. Keywords: Brand Awareness, Vegetables